Individual Learner Support in Digital ELT Courses: Insights from Teacher Education - Jennifer Schluer (Cranmore Publishing, 2020)
Individual support is crucial to help learners improve, but is complicated in times of digital teaching and physical distancing. The present paper demonstrates how individual support can nevertheless be accomplished in digital ELT (English language teaching). It reports on two teacher education courses in Germany that were conducted in a purely digital form as a response to the unprecedented coronavirus situation in 2020. The purpose of these courses was two-fold: On the one hand, the aim was to develop preservice teachers' (PTs') skills of providing individual support to their prospective EFL (English as a foreign language) learners by means of screencast feedback (SCFB). On the other hand, the teacher educator (TE) sought to offer individual support to the PTs in order to promote their feedback skills and advance their English language proficiency even further, especially with respect to academic writing. The multifaceted challenges arising from this complex objective were met through a peer SCFB approach that resorted to a purposeful combination of live webmeetings and individual consultations as well as software tutorials, instructor-generated videos and step-bystep manuals. Also, regular polls and screensharing during the webmeetings helped to keep track of the PTs' progress and understanding. In addition, online surveys gave the PTs room for regular reflection and provided the TE with opportunities for formative assessment. Finally, cognitive, affective and strategic support was offered through group work in digital breakout rooms as well as through individual consultations with the TE and the tutor. Given the novelty of the digital course design, the paper will close with a reflection on its affordances and challenges and suggest potential modifications for future teaching and research.